2016
DOI: 10.5032/jae.2016.03018
|View full text |Cite
|
Sign up to set email alerts
|

Using the Tuning Protocol to Generate Peer Feedback During Student Teaching Lesson Plan Development

Abstract: Self-adequacy during the student teaching experience is high on the list of concerns expressed by student teachers (Fritz & Miller, 2003; Ng, Nicholas, & Williams, 2010). That factor, in combination with others, determines student teachers' goals and sparks their motivation to engage in effective instructional planning (Baylor & Kitsantas, 2005). The purpose of this study was to determine student teachers' perceptions of the use of the tuning protocol, a formalized process of reflective practice and peer revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
0
0
1
Order By: Relevance
“…Según Paulsen et al (2016) los protocolos se uti lizan en el campo de la educación como una guía estructurada para que los grupos de educadores refl exionen formalmente mediante la retroalimentación de sus pares respecto a la planifi cación e implementación de estrategias de instrucción que mejor se adapten a las necesidades de los estudiantes. El protocolo de focalización (en adelante PF) fue creado por Joseph McDonald y sus colegas como parte del Proyecto de Exhibiciones de la Coaliti on of Essencial Schools, para ser uti lizado en los colegios secundarios que parti ciparon en dicho proyecto.…”
Section: El Protocolo: Una Guía Estructurada Para La Retroalimentaciónunclassified
“…Según Paulsen et al (2016) los protocolos se uti lizan en el campo de la educación como una guía estructurada para que los grupos de educadores refl exionen formalmente mediante la retroalimentación de sus pares respecto a la planifi cación e implementación de estrategias de instrucción que mejor se adapten a las necesidades de los estudiantes. El protocolo de focalización (en adelante PF) fue creado por Joseph McDonald y sus colegas como parte del Proyecto de Exhibiciones de la Coaliti on of Essencial Schools, para ser uti lizado en los colegios secundarios que parti ciparon en dicho proyecto.…”
Section: El Protocolo: Una Guía Estructurada Para La Retroalimentaciónunclassified
“…Providing immediate feedback influenced teacher behavior and improved lesson design and pedagogy. Research indicated that preservice teachers valued the feedback received from their peers, and it was especially important in lesson plan development (Paulsen et al, 2016). Teachers deserved the opportunity to engage with informal feedback and reap the rewards, mirroring the systems for student-teachers and preservice teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Policy initiatives in the United States have required or encouraged teachers to collaborate (Kuh, 2016). Teacher collaboration has been explored through the lens of Vygotsky's social constructivist theory, in which the success of a teacher was developed in cooperative environments (Paulsen et al, 2016). The research on feedback was connected to the research on teacher collaboration by way of examination of the critical elements of teacher collaboration: how the culture of the educational site supported it, and how teachers worked together.…”
Section: Collaboration Of Teachersmentioning
confidence: 99%
See 1 more Smart Citation